GROUNDING THE TEXT OF POSTCOLONIALISM: CULTURAL STUDIES AND LITERATURE - Gunia Beniwal, Dr. Sunita Rana (International Journal of Modern Agriculture, 2020)
This research paper aims to introduce Postcolonial theory and its implementation that focuses on the intense interaction between the cultural studies and literature. This piece of writing stresses on defining the terms like- the imperialism, the colonialism and the necolonialism and the postcolonialism in order to emphasize the cultural aspects of postcolonialism. The conception of postcolonialism in the literary field is not the same as imperialism, colonialism and neo-colonialism for the prime centre on culture. In basic, it is an amalgamation of literary study and cultural research which presents new perceptions to revise literary masterpieces from the cultural view point. With the spread of multiculturalism, globalization and cosmopolitanism, to a greater extent the intellects will pursue the pathway of the three pioneers – Edward Said, Gayatri Spivak and Homi K Bhabha. Postcolonialism will persist to be a significant theme for literary studies. And the implementations of postcolonialism, particularly the cultural aspects of it, will outlook the impact of the research of the world literature for an extensive stretch of phase.